2021
DOI: 10.3233/shti210190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Use of Telemedicine Services in an Academic Medical Center

Abstract: The COVID-19 pandemic changed the landscape of telehealth services. The goal of this paper was to identify demographic groups of patients who have used telemedicine services before and after the start of the pandemic, and to analyze how different demographic groups’ telehealth usage patterns change throughout the course of the pandemic. A de-identified study dataset was generated by querying electronic health records at the Mount Sinai Health System to identify all patients. 129,625 patients were analyzed. Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The COVID-19 pandemic accelerated provider and consumer adoption of new digital healthcare technologies. In response, myriad companies have entered the healthcare arena to offer services such as pharmaceutical deliveries, telehealth visits, concierge approaches to primary care, and many other e-health solutions (Appleton et al, 2021; Bitar & Alismail, 2021; Bokolo, 2021; Cui & Finkelstein, 2021; Mann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic accelerated provider and consumer adoption of new digital healthcare technologies. In response, myriad companies have entered the healthcare arena to offer services such as pharmaceutical deliveries, telehealth visits, concierge approaches to primary care, and many other e-health solutions (Appleton et al, 2021; Bitar & Alismail, 2021; Bokolo, 2021; Cui & Finkelstein, 2021; Mann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“… 21–24 The importance of using telerehabilitation has been especially recognized since the start of the COVID-19 pandemic, when its usage has surged in response to social distancing guidelines promulgated by the World Health Organization (WHO). 25 Recent studies have shown its effectiveness in monitoring patients’ progress, ameliorating disease symptoms, and improving clinical outcomes. 2–6 In order to extend physical rehabilitation from a hospital or ambulatory settings to patient homes as a part of routine care of patients with chronic health conditions, 1 successful telerehabilitation programs should support scalable and cost-effective means for prescribing individualized exercise programs, monitoring safety and adherence with exercise, two-way communication between patient and providers, and timely feedback based on patient performance.…”
Section: Introductionmentioning
confidence: 99%
“…The recent rapid spread of coronavirus infection (COVID-19) sparked the interest in the use of m-Health platforms in healthcare ( 3 - 5 ). In fact, telemedicine has been proven as an optimal way to provide medical services due to the possibility to avoid a close contact with infected patients and reduce overall mortality ( 6 - 11 ).…”
Section: Introductionmentioning
confidence: 99%